Multi-target stool DNA test in the surveillance of inflammatory bowel disease: a cross-sectional cohort study. (4th March 2018) - Klepp, Pasquale; Kisiel, John B.; Småstuen, Milada Cvancarova; Røseth, Arne; Andersen, Solveig N.; Vatn, Morten H.; Ahlquist, David A.; Moum, Bjørn A.; Brackmann, Stephan
Abstract: Background and aim: Colonoscopic surveillance is recommended in patients with longstanding inflammatory bowel disease (IBD) as they are at increased risk of colorectal cancer (CRC). Non-invasive surveillance may improve compliance and access. Multi-target stool DNA (MT-sDNA) has been validated for screening of sporadic CRC but has not been assessed in IBD. Our aim was to assess the performance of a MT-sDNA test in a real-life surveillance setting of patients with longstanding IBD. Material and methods: A total of 192 IBD patients enrolled from two prospective cohorts submitted an EDTA buffered stool sample and underwent chromo- or white light colonoscopy. Stools were assayed for methylated BMP3 & NDRG4, mutant KRAS and β-actin by a laboratory blinded to clinical data. Results: The multitarget-sDNA panel was positive in 2/2 CRC and 5/15 low-grade dysplasia (LGD) < 1 cm in diameter. Sensitivities were 100% (95% CI 16–100%) for CRC and 33% (95% CI 13–61%) for LGD lesions <1 cm, with specificities of 87% (95% CI 81–91%) and 93% (95% CI 88–96%), respectively. The estimated number of patients needed to screen to detect a single CRC was 96 (95% CI 93–99%) and was 28 (95% CI 22–34%) to detect any colorectal neoplasia (CRN). Conclusion: The MT-sDNA panel detected CRC in IBD. Sensitivity for sub-centimeter colorectal neoplasms in IBD patients appears similar to that observed in the general population. The test may be a valuable tool for detection of malignancy during structured surveillance of long-term IBD in a first line hospital setting.